2020
DOI: 10.1002/jbm.a.37076
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow coagulated and low‐level laser therapy accelerate bone healing by enhancing angiogenesis, cell proliferation, osteoblast differentiation, and mineralization

Abstract: The present study evaluated bone marrow aspirate (BMA) and low‐level laser therapy (LLLT) on bone healing. It was created critical‐size defects (CSD) of 5 mm diameter in rat calvaria of 64 rats. Animals were randomly divided into four groups: Control (blood clot), BMA (coagulated BMA), LLLT (laser irradiation and blood clot), and BMA/LLLT (laser irradiation and coagulated BMA). Euthanasia was performed at 15 or 30 days postoperative. Immunohistochemical reactions were performed to identify vascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 61 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…These studies demonstrated that BMA can be a useful tool to promote bone formation. It is possible that the positive bone regeneration results observed in groups treated with BMA in the selected studies were due to a significant increase in MSC at the surgical site (Santinoni et al, 2021;Nagata et al, 2013). This hypothesis is supported by the findings of Smiler et al (2008) who analyzed samples of BMA of patients aged 23-73 years by flow cytometry analysis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These studies demonstrated that BMA can be a useful tool to promote bone formation. It is possible that the positive bone regeneration results observed in groups treated with BMA in the selected studies were due to a significant increase in MSC at the surgical site (Santinoni et al, 2021;Nagata et al, 2013). This hypothesis is supported by the findings of Smiler et al (2008) who analyzed samples of BMA of patients aged 23-73 years by flow cytometry analysis.…”
Section: Discussionmentioning
confidence: 73%
“…Using unprocessed cells can strength therapeutic potential and avoid treatment delay and extensive costs associated with cultivation steps (Bara et al, 2014). Therefore, studies have evaluated the use of BMA in bone healing, either alone or combined with other therapeutic modalities (Santinoni et al, 2021;Nagata et al, 2013;Bansal et al, 2009;Soltan et al, 2007), with promising results. Besides MSC, BMA contains a substantial amount of hematopoietic and endothelial stem cells (Smiler et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PBM therapy results in the photochemical interaction of light with cellular constituents promoting the acceleration of cell function. It is capable of modulating osteogenesis from the stimulus for the differentiation of bone marrow mesenchymal cells ( 21 ) and activating osteoblasts, inducing their proliferation ( 22 ) and thus increase the effectiveness of PBM in bone formation ( 23 ). This was confirmed in the present study in the groups treated with PBM therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that LPL-mediated PBM is able to increase the blood supply in the injury area, through the formation of new blood vessels (angiogenesis) ( 23 ). Oxygen plays an important role in all repair phases, due to its ability to contribute to the occurrence of angiogenesis, cell proliferation, bacterial reduction and collagen synthesis ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low-level laser therapy (LLLT) or photobiomodulation was first discovered by accident when the Hungarian physician Endre Mester tried using it as treatment for tumors only to find that it resulted in stimulating hair regrowth and wound healing in rats [335]. Since then, it was proven to be an effective biostimulant and was investigated for multiple application including bone regeneration [336][337][338][339][340][341][342][343][344][345][346] and angiogenesis [347][348][349][350]. The effect of photobiomodulation was also studied in DSCs.…”
Section: Environmental Stimulators Regulating Osteogenesis In Dental Stem Cellsmentioning
confidence: 99%